Rethinking 2S/LGBTQI+ food security with co-design: a study protocol - Thériault, Joanie; Joy, Phillip; Boudhraâ, Sana; Gao, Min (Frontiers in Public Health, 2025)
ContextIn Canada, recent statistics show that 8.7 million Canadians face food insecurity which disproportionately affects people of the 2S/LGBTQI+ communities. Food insecurity is intersectional: people belonging to one or more marginalized groups, like 2S/LGBTQI+, are at greater risk. Moreover, food security resources can pose due to the stigma and cis-heterosexism associated with the religious basis of some of these resources. Exploring ways to partner up with and for 2S/LGBTQI+ communities and food security organizations in order to reflect and imagine a new service model is a promising avenue to tackle the social injustice of food insecurity.ObjectivesThis research protocol presents the activities and strategies of a co-design study aiming to enhance safety and inclusivity of food security services with and for 2S/LGBTQI+ individuals. The team also seeks to identify how to improve food security services with and for 2S/LGBTQI+ communities and to co-create a prototype service model representing safe and inclusive services that communities and food security stakeholders can utilize to make improvements in that direction.MethodsThis protocol is based on a co-design methodology inspired by design thinking. The project will address desirability, feasibility, and viability - what is desirable, acceptable, achievable and sustainable in a prototype service model for 2S/LGBTQI+ individuals accessing food security services, organizations, and workers/volunteers. Participants will take part in seven online co-design workshops. Facilitators will guide the participants in offering free commentary, generating thoughts, and sharing new ideas along with reflective questions regarding a provisional prototype of the service model and framework principles. Discussions will be recorded for analysis purposes along with visual and textual content generated through the web-based collaborative tool. The data will be subjected to a qualitative thematic analysis.ConclusionThis protocol recognizes and values the experience and knowledge of 2S/LGBTQI+ communities and illustrates participatory involvement to improve food security. It is expected that this protocol inspires researchers and organizations to partner up and explore ways to use, replicate, and improve or adapt the approach. Future results may find interest and usefulness in other 2S/LGBTQI+ communities and food security organizations.